The KIR repertoire of a West African chimpanzee population is characterized by limited gene, allele, and haplotype variation - de Groot, Natasja G.; Heijmans, Corrine M.C.; van der Wiel, Marit K.H.; Bruijnesteijn, Jesse; Bontrop, Ronald E. (Frontiers in Immunology, 2023)
The killer cell immunoglobulin-like receptors (KIR) play a pivotal role in modulating the NK cell responses, for instance, through interaction with major histocompatibility complex (MHC) class I molecules. Both gene systems map to different chromosomes but co-evolved during evolution. The human KIR gene family is characterized by abundant allelic polymorphism and copy number variation. In contrast, our knowledge of the KIR repertoire in chimpanzees is limited to 39 reported alleles, with no available population data. Only three genomic KIR region configurations have been mapped, and seventeen additional ones were deduced by genotyping.Previously, we documented that the chimpanzee MHC class I repertoire has been skewed due to an ancient selective sweep. To understand the depth of the sweep, we set out to determine the full-length KIR transcriptome -in our MHC characterized pedigreed West African chimpanzee cohort -using SMRT sequencing (PacBio). In addition, the genomic organization of 14 KIR haplotypes was characterized by applying a Cas9-mediated enrichment approach in concert with long-read sequencing by Oxford Nanopore Technologies. In the cohort, we discovered 35 undescribed and 15 already recorded Patr-KIR alleles, and a novel hybrid KIR gene. Some KIR transcripts are subject to evolutionary conserved alternative splicing events. A detailed insight on the KIR region dynamics (location and order of genes) was obtained, however, only five new KIR region configurations were detected. The population data allowed to investigate the distribution of the MHC-C1 and C2-epitope specificity of the inhibitory lineage III KIR repertoire, and appears to be skewed towards C2. Although the KIR region is known to evolve fast, as observed in other primate species, our overall conclusion is that the genomic architecture and repertoire in West African chimpanzees exhibit only limited to moderate levels of variation. Hence, the ancient selective sweep that affected the chimpanzee MHC class I region may also have impacted the KIR system.